Depressive symptoms and quality of life in older adults’ population: quantitative and qualitative approaches - Santos, Ana João (2015)
Based on a national prevalence study “Ageing and Violence”, within the Portuguese population aged 60+, in family context, this presentation reflects upon depressive symptoms in older age. Depressive disorder is one of the most frequent illnesses among older people, impacting negatively on their quality of life and well-being. Frequently underreported, depression may present itself with somatic and functional complaints similar to other illnesses or be devalued as “normal” adjustment to the changes that often come in later life (retirement, the death of loved ones, increased isolation, and medical problems). The data derives from the exploratory phase of the study, where semi-structured interviews (N=13) and Focus-group (N=60) were employed. In addition we also collected quantitative data on a nationally representative probability sample of dwelling adults aged 60 and over (N=1123). A 5-item version of the Geriatric Depression Scale was used to screen for depressive symptoms. Overall, 51.3% of the older adults living in private households reported depressive symptoms. These were associated with long-term illness morbidity (p<0.001), reliance on help with ADLs (p<0.001), gender (p<0.001), socio-economic status (p<0.001) and absence of supportive social networks (p=0.005). In accordance, focus group and interviews participants also indicated illness and the need of help to perform day to day activities as major hurdles to well-being. Loneliness was highlighted as the most significant factor to interfere with quality of life in older age. As we grow older, we face significant life changes that can put us at risk for depression. However, depression is not an inevitable part of ageing, even though several factors, present in the lives of many elderly, can be a contributing factor to this disorder. Quantitative data and qualitative data indicate social exclusion as a crucial aspect that may protect or put at risk older adults in developing this disorder.